The Need Assessment in Developing Teacher Innovator’s Skills under the Office of the Basic Education Commission - Koson Pusri; Pacharawit Chansirisira (Journal of Educational Issues, 2024)
The primary research goals, as set forth by the Office of the Basic Education Commission, were to 1) examine the elements and indicators of secondary school teachers’ innovative talents. 2) To examine the requirement for secondary school teacher innovation skills development within the Office of the Basic Education Commission. The findings were validated and confirmed by nine specialists. In the northeastern zone of the Office of the Basic Education Commission, 540 school principals and teachers were selected as the sampling group using a multi-stage random sampling process. Mean, standard deviation, and the Priority Needs Index were used to analyze the data. The findings indicated that school teachers’ innovator skills consist of 5 celements, including initiative skills with five indicators, questioning skills with 6 indicators, observation skills with 6 indicators, experimental skills with 6 indicators, and 5) networking skills with 5 indicators. The degree of appropriateness for the components and indicators is quite high. Need assessment for building teacher innovators’ skills revealed that the aspect with the greatest demand was questioning skills, with initiative skills, observation skills, experimental skills, and networking skills coming in second and third, respectively. The overall state of the Office of the Basic Education Commission’s secondary school teachers’ innovative skills is currently at a medium level; the component with the highest average score was networking skills, followed by trial skills, initiative skills, questioning skills, and observation skills, in that order. The aspect with the highest average score was trial skills, followed by questioning skills, initiative skills, observation skills, and networking skills in that order, which are all at the highest degree of desired condition.